2005
DOI: 10.1097/01.mcg.0000173853.78042.2d
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of Serologic Markers in Children With IBD

Abstract: Despite our homogeneous patient population, pANCA and ASCA antibodies had an inadequate sensitivity/specificity for children with UC or CD. Those antibodies were not useful for our small number of patients with IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…A fact which may itself reflect a distinct clinicoserological entity is that 48.5% of patients do not show antibodies against either ASCA or pANCA 98 . Whilst some subsequent studies have cast doubts over the usefulness of these markers, many have concurred with the original findings 99–103 …”
Section: Ic Ancillary Tests and The Futurementioning
confidence: 97%
See 1 more Smart Citation
“…A fact which may itself reflect a distinct clinicoserological entity is that 48.5% of patients do not show antibodies against either ASCA or pANCA 98 . Whilst some subsequent studies have cast doubts over the usefulness of these markers, many have concurred with the original findings 99–103 …”
Section: Ic Ancillary Tests and The Futurementioning
confidence: 97%
“…98 Whilst some subsequent studies have cast doubts over the usefulness of these markers, many have concurred with the original findings. [99][100][101][102][103] Molecular studies amplifying Yersinia DNA from CD resection specimens have shown up to 31% positivity. However, further studies are needed to determine whether the presence of Yersinia DNA is an epiphenomenon or a feature of CD pathogenesis.…”
Section: Serological Markersmentioning
confidence: 99%
“…Things may be different in children with IBD, where these tests could be clinically useful to differentiate between IBD and other diarrheal illnesses [1, 5]. Actually, many [6,7,8,9,10,11,12,13,14,15] but not all [16] available studies in IBD pediatric populations reported that testing for these antibodies yields significantly useful clinical information and may avoid further unnecessary examinations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, independent studies have reported poor sensitivity for OmpC IgA in IBD, and false positives are common (6,43).…”
mentioning
confidence: 99%